ALIH KODE DALAM DIALOG NOVEL SURGA YANG TAK DIRINDUKAN KARYA ASMA NADIA - Rina Wulandari; Sri Marmanto; Sumarlam Sumarlam (Prasasti: Journal of Linguistics, 2016)
The objectives of this research are to explain: (1) the forms of code switching in a dialogue of novel Surga yang Tak Dirindukan, (2) the factors influencing of code switching in a dialogue of novel Surga yang Tak Dirindukan, (3) the functions of code switching in a dialogue of novel Surga yang Tak Dirindukan.